VD_FINDINFO Décision / 2012 / 526 vom 19. März 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)